Effect of Lateral Aspect Ratio on Three-Dimensional Double Diffusive Convection in Porous Enclosures with Opposing Temperature and Concentration Gradients - Mohamad, Abdulmajeed Abd; Sezai, Ibrahim (My University, 2002)
In a recent work performed by the authors on the buoyant flow in a cubic porous cavity with opposing horizontal temperature and concentration gradients, it was found that the flow structure becomes three-dimensional for certain parameter ranges. Superimposed on the main flow rotation, a secondary flow is set up in the transverse planes, which 2D models fail to capture. The rate of heat and mass transfer predicted by the 2D models does not reflect the true values for certain parameter ranges where the flow structure is three-dimensional. The present investigation aims to study the effect of lateral aspect ratio on the flow structure and rate of heat transfer. Interestingly, it is found that as the lateral aspect ratio increases by a facor of integer numbers (i.e., 2, 3, 4, ...) the flow structure found in the cubic cavity repeats itself in a lateral direction.
Keywords: Buoyancy; Insulating materials; Mathematical models; Parameter estimation; Thermal gradients; Waste disposal; Concentration gradients; Heat convection